Second act : a novel [large type] - Steel, Danielle (Random House Large Print, 2023)
As the head of a prestigious movie studio for nearly two decades, Andy Westfield has had every conceivable professional luxury: a stunning office on the forty-fourth floor, a loyal assistant who can all but read his mind, access to a private jet and company cars. The son of Hollywood royalty, Andy always put his career before his marriage, and now, besides his daughter and young grandchildren, it's the only thing he truly loves. But then Andy's world is upended. The studio is sold, and the buyer's son demands the top seat. Out of a job and humiliated, Andy spirals. When his head clears, he decides to get as far away from Los Angeles as possible until the dust settles and he can find a new way forward. Andy signs a six-month rental agreement for a luxurious home in a tiny, forgotten coastal town two hours from London. When he arrives, he hires a local woman to help get his affairs in order. A former journalist, Violet Smith is at a crossroads as well, and this temporary job is exactly what she needs to tide her over. But when Violet leaves the manuscript of her unfinished novel behind after work one day, Andy lets his curiosity get the best of him and is captivated by a story that begs to be adapted for the big screen. Could this be the miracle they've both been looking for?